2003
DOI: 10.1017/s0016672303006268
|View full text |Cite
|
Sign up to set email alerts
|

Conserved fragments of transposable elements in intergenic regions: evidence for widespread recruitment of MIR- and L2-derived sequences within the mouse and human genomes

Abstract: We analysed the distribution of transposable elements (TEs) in 100 aligned pairs of orthologous intergenic regions from the mouse and human genomes. Within these regions, conserved segments of high similarity between the two species alternate with segments of low similarity. Identifiable TEs comprise 40-60% of segments of low similarity. Within such segments, a particular copy of a TE found in one species has no orthologue in the other. Overall, TEs comprise only approximately 20 % of conserved segments. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 38 publications
10
56
0
1
Order By: Relevance
“…Transposable elements contain a variety of functional subunits that can be exapted and modified by the host genome 89,91 , and they can mediate duplication of existing CNEs to distant genomic locations through transduction or chimaerism 92 . Individual instances of CNEs derived from transposable elements have been described previously 14,94,95 . However, these cases together comprise only a trivial fraction of the CNEs in the human genome.…”
Section: Conserved Sequence Elementsmentioning
confidence: 99%
“…Transposable elements contain a variety of functional subunits that can be exapted and modified by the host genome 89,91 , and they can mediate duplication of existing CNEs to distant genomic locations through transduction or chimaerism 92 . Individual instances of CNEs derived from transposable elements have been described previously 14,94,95 . However, these cases together comprise only a trivial fraction of the CNEs in the human genome.…”
Section: Conserved Sequence Elementsmentioning
confidence: 99%
“…First of all, a number of noncoding MIR sequences were found to be highly conserved, indicative of some functional, presumably regulatory, role (24). Later, it was shown that MIRs are enriched for open chromatin sites (25), encode regulatory RNAs (26), host gene promoters (27) and enhancers (28), and are also associated with tissue-specific expressed genes (29).…”
Section: Significancementioning
confidence: 99%
“…Eutherian ARs are fragments of mobile elements believed to have inserted into the common ancestor of all placental mammals and been retained since then. Assuming these elements are largely not functional, they are free to evolve in the absence of selection (with notable exceptions: Nekrutenko and Li 2001;Jordan et al 2003;Silva et al 2003;Cooper et al 2005;Kamal et al 2006) and thus constitute a good model for neutral evolution in mammalian genomics (International Mouse Genome Sequencing Consortium 2002;Ellegren et al 2003;Hardison et al 2003;Rat Genome Sequencing Project Consortium 2004;Yang et al 2004). First, we note that rates of evolution in ARs are similar to, but higher than, rates estimated from fourfold degenerate sites within proteins (average increases of 2%-13%, depending on the alignment and region).…”
Section: Alignment Comparison-nucleotide Levelmentioning
confidence: 99%
“…Coding exons are generally true positives, for example, but are well known to be a nonrepresentative minority of the total space of constrained sequence. On the other hand, ancestral repeats are generally thought to evolve neutrally, but have been previously shown to include a nontrivial amount of constrained DNA (Silva et al 2003;Cooper et al 2005;Kamal et al 2006). We therefore adopted an empirical approach to measure and standardize falsediscovery rates that can also effectively cope with both region and alignment variation in the underlying neutral rates, similar to a previously described method .…”
Section: Standardizing False-discovery Ratesmentioning
confidence: 99%